2021
DOI: 10.3390/ijms221810091
|View full text |Cite
|
Sign up to set email alerts
|

Design and Engineering of “Green” Nanoemulsions for Enhanced Topical Delivery of Bakuchiol Achieved in a Sustainable Manner: A Novel Eco-Friendly Approach to Bioretinol

Abstract: In the present work, we establish novel “environmentally-friendly” oil-in-water nanoemulsions to enhance the transdermal delivery of bakuchiol, the so-called “bioretinol” obtained from powdered Psoralea corylifolia seeds via a sustainable process, i.e., using a supercritical fluid extraction approach with pure carbon dioxide (SC-CO2). According to Green Chemistry principles, five novel formulations were stabilized by “green” hybrid ionic surfactants such as coco-betaine—surfactin molecules obtained from coconu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Extraction of bakuchiol with advanced methods was rarely explored. A study on ultrasonic assisted 23 and supercritical CO 2 extraction 24 of bakuchiol reported highest yield when compared with other conventional methods. Further, many advanced extraction techniques (microwaves, ultrasonic, pressurized liquids, supercritical fluids, and electric fields etc. )…”
Section: Occurrence and Isolationmentioning
confidence: 96%
“…Extraction of bakuchiol with advanced methods was rarely explored. A study on ultrasonic assisted 23 and supercritical CO 2 extraction 24 of bakuchiol reported highest yield when compared with other conventional methods. Further, many advanced extraction techniques (microwaves, ultrasonic, pressurized liquids, supercritical fluids, and electric fields etc. )…”
Section: Occurrence and Isolationmentioning
confidence: 96%
“…When compared to other compounds derived from P. coryliforia , (BAK, 8‐MOP, ipsoralen, and psoralidin) in an in vitro study, BAK showed moderate keratinocyte antiproliferative activity, with MOP and ipsoralen with the highest counts 16 . Additionally, BAK was shown to be highly lipophilic, for which an oil‐in‐water nanoemulsion was developed to enhance its transdermal delivery 17 …”
Section: Resultsmentioning
confidence: 99%
“…16 Additionally, BAK was shown to be highly lipophilic, for which an oil-in-water nanoemulsion was developed to enhance its transdermal delivery. 17 Bakuchiol was also studied to elucidate its immunomodulatory and anti-inflammatory mechanisms in macrophage cell lines, showing that it significantly suppressed the pro-inflammatory cytokine expression in a dose-dependent manner. 18 Also, oral administration per healthy mice significantly decreased delayed hypersensitivity responses as compared to control group.…”
Section: Other Applicationsmentioning
confidence: 99%
“…To produce cosmetics containing bakuchiol is used bakuchiol carrier oil or about 90% pure bakuchiol which is achieved through an extraction process. Bakuchiol extract purification 4 , 6 , 15 involves several different steps and is not always completely effective. Up to now, a few methods based on high-performance liquid chromatography (HPLC) with various types of detection have been developed for bakuchiol determination in Psoralea corylifolia 4 , 16 22 .…”
Section: Introductionmentioning
confidence: 99%